2011
DOI: 10.1021/la2016726
|View full text |Cite
|
Sign up to set email alerts
|

Site Competition during Coadsorption of Acetone with Methanol and Water on TiO2(110)

Abstract: The competitive interaction between acetone and two solvent molecules (methanol and water) for surface sites on rutile TiO(2)(110) was studied using temperature-programmed desorption (TPD). On a vacuum-annealed TiO(2)(110) surface, which possessed ~5% oxygen vacancy sites, excess methanol displaced preadsorbed acetone molecules to weakly bound and physisorbed desorption states below 200 K. In contrast, acetone molecules were stabilized on an oxidized surface against displacement by methanol through formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 72 publications
(113 reference statements)
2
19
0
Order By: Relevance
“…This observation points to a deactivation of TiO 2 , presumably due to the exposure to water vapor produced during the co-feeding experiment. It was reported that for acetone adsorption on TiO 2 water has an inhibiting effect [86]. It seems reasonable to assume that during 2-propanol oxidation over TiO 2 water blocks the active sites for oxidation and, as a result, less oxidation to acetone takes place.…”
Section: Discussionmentioning
confidence: 97%
“…This observation points to a deactivation of TiO 2 , presumably due to the exposure to water vapor produced during the co-feeding experiment. It was reported that for acetone adsorption on TiO 2 water has an inhibiting effect [86]. It seems reasonable to assume that during 2-propanol oxidation over TiO 2 water blocks the active sites for oxidation and, as a result, less oxidation to acetone takes place.…”
Section: Discussionmentioning
confidence: 97%
“…Such site competition between two or more adsorbates can suppress reaction rates and thus alter reaction pathways. 3 Therefore, a molecular level understanding of the competition phenomena of the reactants, intermediates and/or products around the active sites on the catalyst surfaces is a fundamentally crucial aspect in elucidating the heterogeneous catalytic reaction mechanisms and thus guiding the design of new catalysts and catalytic reactions. [4][5][6] Due to the excellent properties in heterogeneous catalysis, titanium dioxide (TiO 2 ) has attracted considerable attention in many fields, such as photo-induced water splitting, air purification and solar fuel cells in the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Studies on competitive adsorption onto TiO 2 (110) at the atomic or molecular scale under ultra-high vacuum (UHV) conditions provide an excellent benchmark for understanding the more complex, realworld heterogeneous catalytic reactions. 2,3,10 Shen and Henderson studied the site competition during co-adsorption of acetone with methanol and water onto TiO 2 (110) by using temperature programmed desorption (TPD). 3 Smith et al investigated the adsorption, desorption, and displacement kinetics of H 2 O and CO 2 on TiO 2 (110) and pointed out that the relative strength of adsorption is the dominant factor of the competitive adsorption kinetics in their discussions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6(a) compares the TPD spectra of the 8, 15 and 30 nm films. The TPD data show a two stage water desorption process, one at low temperature (around 100-120 • C) and the second, more important stage with a strain dependent onset between 315 and 350 • C. This is clear evidence for the presence of dissociatively adsorbed water on the surface whereas the smaller proportion of physisorbed molecular water is desorbed at 100-120 • C [15,16]. Similar desorption features are observed for the three films except for a variation in the onset of the main peak.…”
Section: Resultsmentioning
confidence: 86%